Population subdivision of hydrothermal vent polychaete Alvinella pompejana across equatorial and Easter Microplate boundaries. Issue 1 (December 2016) - Jang, Sook-Jin; Park, Eunji; Lee, Won-Kyung; Johnson, Shannon; Vrijenhoek, Robert; Won, Yong-Jin
Abstract Background The Equator and Easter Microplate regions of the eastern Pacific Ocean exhibit geomorphological and hydrological features that create barriers to dispersal for a number of animals associated with deep-sea hydrothermal vent habitats. This study examined effects of these boundaries on geographical subdivision of the vent polychaeteAlvinella pompejana . DNA sequences from one mitochondrial and eleven nuclear genes were examined in samples collected from ten vent localities that comprise the species' known range from 23°N latitude on the East Pacific Rise to 38°S latitude on the Pacific Antarctic Ridge. Results Multi-locus genotypes inferred from these sequences clustered the individual worms into three metapopulation segments — the northern East Pacific Rise (NEPR), southern East Pacific Rise (SEPR), and northeastern Pacific Antarctic Ridge (PAR) — separated by the Equator and Easter Microplate boundaries. Genetic diversity estimators were negatively correlated with tectonic spreading rates. Application of the isolation-with-migration (IMa2) model provided information about divergence times and demographic parameters. The PAR and NEPR metapopulation segments were estimated to have split roughly 4.20 million years ago (Mya) (2.42–33.42 Mya, 95 % highest posterior density, (HPD)), followed by splitting of the SEPR and NEPR segments about 0.79 Mya (0.07–6.67 Mya, 95 % HPD). Estimates of gene flow between the neighboring regions were mostly low (2 Nm  < 1). Estimates of effective population size decreased with southern latitudes: NEPR > SEPR > PAR. Conclusions Highly effective dispersal capabilities allowA. pompejana to overcome the temporal instability and intermittent distribution of active hydrothermal vents in the eastern Pacific Ocean. Consequently, the species exhibits very high levels of genetic diversity compared with many co-distributed vent annelids and mollusks. Nonetheless, its levels of genetic diversity in partially isolated populations are inversely correlated with tectonic spreading rates. As for many other vent taxa, this pioneering colonizer is similarly affected by local rates of habitat turnover and by major dispersal filters associated with the Equator and the Easter Microplate region.